A one-step multiplex PCR-based assay for simultaneous detection and classification of virulence factors to identify five diarrheagenic E. coli pathotypes - Mari Ohmura-Hoshino; Yuki Miyaki; Shigeko Yashima (Heliyon, 2022)
Human diarrhea-causing strains of Escherichia coli are referred to as diarrheagenic E. coli (DEC). DEC can be divided into five main categories based on distinct epidemiological and clinical features, specific virulence determinants, and association with certain serotypes. In the present study, a simple and rapid one-step single reaction multiplex PCR (mPCR) assay was developed for the simultaneous identification and differentiation of five currently established DEC pathotypes causing gastrointestinal diseases. The mPCR incorporated 10 primer pairs to amplify 10 virulence genes specific to the different pathotypes (i.e., stx1 and stx2 for EHEC, elt and sth for ETEC, eaeA and bfpA for EPEC, aggR and astA for EAEC, and ipaH and invE for EIEC) and to generate DNA fragments of sufficiently different sizes to be unequivocally resolved. All strains were detected at concentrations ranging from 104 to 107 CFU/mL. To demonstrate the utility of the mPCR assay, 236 clinically isolated strains of DEC from two hospitals were successfully categorized. One-step mPCR technique reduced the cost and effort involved in the identification of various virulence factors in DEC. Thus, we demonstrated that the newly developed mPCR assay has the potential to be introduced as a diagnostic tool that can be utilized for the detection of DEC as an additional check in clinical laboratories and for confirmation in health and environment institutes, health centers, and reference laboratories.